2021
DOI: 10.1016/j.ejca.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in young adult survivors of childhood cancer – A population-based study

Abstract: To determine the prevalence of sexual dysfunction and to identify the factors associated with sexual dysfunction in young adult childhood cancer survivors. Methods: All survivors of childhood cancer (aged 19e40 years) in Sweden were invited to this population-based study, and 2546 men and women (59%) participated. Sexual function was examined with the PROMIS Sexual Function and Satisfaction Measure. Logistic regression was used to assess the differences between survivors and a general population sample (n Z 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 36 publications
(60 reference statements)
3
54
0
Order By: Relevance
“…Similar to a recent study from Sweden including adult childhood cancer survivors 35 and findings in healthy adolescents in the general population of Switzerland, 29 we found that female survivors were more likely to have a more negative body image than male survivors. This confirms the extensive literature on sex differences in body image, indicating that females are more likely to negatively self‐evaluate their appearance and report higher levels of body image dissatisfaction than men 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to a recent study from Sweden including adult childhood cancer survivors 35 and findings in healthy adolescents in the general population of Switzerland, 29 we found that female survivors were more likely to have a more negative body image than male survivors. This confirms the extensive literature on sex differences in body image, indicating that females are more likely to negatively self‐evaluate their appearance and report higher levels of body image dissatisfaction than men 14 .…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with a study from the Netherlands including adult survivors 9 and a previous systematic review including quantitative and qualitative studies and patients on active treatment. 13 Similar to a recent study from Sweden including adult childhood cancer survivors 35 and findings in healthy adolescents in the general population of Switzerland, 29 we found that female survivors were more likely to have a more negative body image than male survivors.…”
Section: Discussionsupporting
confidence: 87%
“…19 Evidence from other studies including adolescent long-term childhood cancer survivors is limited by lack of population-based sampling approaches and restrictions to certain cancer types. [35][36][37] Similar to a recent study from Sweden including adult childhood cancer survivors 20 and findings in healthy adolescents in the general population of Switzerland, 28 we found that female survivors were more likely to have a more negative body image than male survivors. This confirms the extensive literature on sex differences in body image indicating that females are more likely to negatively self-evaluate their appearance and report higher levels of body image dissatisfaction than men.…”
Section: Discussionsupporting
confidence: 89%
“…[15][16][17][18] However, a systematic review from 2009 concluded that there is no consistent evidence regarding differences in body image between children and adolescents with cancer and healthy controls. 19 A recent study from Sweden indicated higher body image disturbance in adult women who survived childhood cancer compared to the cancer-free women 20 while another study from the Netherlands found no differences. 9 However, evidence from studies including adolescent childhood cancer survivors is sparse and it remains unclear how chronic health conditions affect the body image of long-term survivors.…”
Section: Introductionmentioning
confidence: 98%
“…This observation reflects the multitude of bio‐psycho‐social factors associated with partnering and having children. The importance of being able to form long‐lasting relationships for the chance of pregnancy is clinically significant considering that previous reports have found cancer survivors to be less likely to partner in adulthood 11,19 …”
Section: Discussionmentioning
confidence: 99%